Polish-German Dispute over WWII Reparations - Rafał Adamus (Societas et Iurisprudentia, 2023)
This study concerns the dispute between Poland and Germany regarding war reparations for losses caused in Poland in the years 1939 – 1945. The author pointed to the relevant acts of international law. This applies to the so-called Potsdam Agreement, the declaration of the Union of Soviet Socialist Republics (hereinafter referred to as the “USSR”) on the resignation of claims against Germany, the declaration of the government of the People’s Republic of Poland on the resignation of claims, the German unification treaty. As well as in the study, the substantive position that may be presented by Poland was indicated. After the end of the World War II, there was no peace agreement between the defeated Germans and members of the anti-German coalition. This was due to emerging political differences between the victorious states. What is significant in the case is the fact that the Polish war losses were not covered in full. There are reasons to believe that Poland’s renunciation of claims in year 1953 (with effect from January 1, 1954) was invalid.